Queuing Theory to Manage Electronic Business - Arshi Naim (Scholars Digest Publishing, 2022)
The pandemic spread due to novice disease Coronavirus has changed the entire social environment. Social as well as commercial lives have extensively got affected especially small entrepreneurs and small stores in working physical environment have to suffer a serious loss. This study is an attempt to facilitate small stores in working efficiently in the physical environment while keep social distancing for all the customers in the small stores. The study show how technologies can help in maintaining social distancing and carrying out entire buying process effectively. The study is based on electronic queue system and suggests how small stores can install this system to prevent the spread and achieve good returns.